2018
DOI: 10.1186/s12879-018-3427-8
|View full text |Cite
|
Sign up to set email alerts
|

The role of socioeconomic and climatic factors in the spatio-temporal variation of human rabies in China

Abstract: BackgroundRabies is a significant public health problem in China. Previous spatial epidemiological studies have helped understand the epidemiology of animal and human rabies in China. However, quantification of effects derived from relevant factors was insufficient and complex spatial interactions were not well articulated, which may lead to non-negligible bias. In this study, we aimed to quantify the role of socio-economic and climate factors in the spatial distribution of human rabies to support decision mak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 37 publications
4
33
0
Order By: Relevance
“…In the long-run, an approximate increase by 0.7916 rabies case per month is expected in Davao City if the temperature of the preceding month remains on the average at 28.27˚C (i.e., 0.0280 � 28.27 = 0.7916). A similar finding has been observed for human rabies cases in China [48][49][50]. Increased dog activity on months with high temperatures is a probable cause of the rise in the number of dog bites [50].…”
Section: Plos Onesupporting
confidence: 81%
See 1 more Smart Citation
“…In the long-run, an approximate increase by 0.7916 rabies case per month is expected in Davao City if the temperature of the preceding month remains on the average at 28.27˚C (i.e., 0.0280 � 28.27 = 0.7916). A similar finding has been observed for human rabies cases in China [48][49][50]. Increased dog activity on months with high temperatures is a probable cause of the rise in the number of dog bites [50].…”
Section: Plos Onesupporting
confidence: 81%
“…Temperature is a potential risk factor of rabies spread as the dog's temper is sensitive to high temperatures [48]. Furthermore, animals are more active and travel with greater distance at warmer temperatures, thereby contributing to rabies spread especially with warmer climate [49].…”
Section: Plos Onementioning
confidence: 99%
“…Main roads and rivers were previously found to directly influence the distribution of domestic dogs (Brunker et al., 2018; Onyango et al, Sahin, Awiti, Chu, & Mackey, 2016; Patz et al, Olson, Uejio, & Gibbs, 2008; Zarza et al, Martínez‐Meyer, Suzán, & Ceballos, 2017). In general, the farther a place is from a main road, the more difficult it is to implement public health interventions (Guo, Yin, et al, 2018) and dog vaccination campaigns (Wera et al, Mourits, & Hogeveen, 2015), and as a consequence, the higher the risk of human rabies following bites by RABV‐infected dogs. In contrast, our study showed that the closer of areas to a main road, the higher the risk of human rabies cases.…”
Section: Discussionmentioning
confidence: 99%
“…Human rabies distribution is associated with environmental factors such as temperature (positive correlation) and elevation (negative correlation) (Guo, Yin, et al, 2018). Environmental factors also play a key role in the occurrence of rabies vectored by other mammals, such as raccoons and striped skunks (Brunker et al., 2018; Recuenco et al, Eidson, Cherry, Kulldorff, & Johnson, 2008; Russell et al, Real, & Smith, 2006; Smith et al, Lucey, Waller, Childs, & Real, 2002; Smith et al, Waller, Russell, Childs, & Real, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, more and more public health researchers have begun to apply the spatial analysis methods to investigate the influencing factors of diseases related with environmental health and environmental pollution [ 22 , 23 ], it was a trend to merge different spatial effect socio-economic indicators into the panel data model for analyzing the influencing factors of ISRs. However, there is a lack of research that has scientifically analyzed the spatial pattern and spatiotemporal characteristics of ISR, and possible factors that influencing ISRs over time.…”
Section: Introductionmentioning
confidence: 99%